Modulation of Dormancy and Growth Responses in Reproductive Buds of Temperate Trees - Lloret, Alba; Badenes, María L.; Ríos, Gabino (2019)
During autumn perennial trees cease growth and form structures called buds in order to protect meristems from the unfavorable environmental conditions, including low temperature and desiccation. In addition to increased tolerance to these abiotic stresses, reproductive buds modulate developmental programs leading to dormancy induction to avoid premature growth resumption, and flowering pathways. Stress tolerance, dormancy, and flowering processes are thus physically and temporarily restricted to a bud, and consequently forced to interact at the regulatory level.We review recent genomic, genetic, and molecular contributions to the knowledge of these three processes in trees, highlighting the role of epigenetic modifications, phytohormones, and common regulatory factors. Finally, we emphasize the utility of transcriptomic approaches for the identification of key structural and regulatory genes involved in bud processes, illustrated with our own experience using peach as a model.